Hybrid modification of high‐density polyethylene with hyperbranched polyethylene‐functionalized multiwalled carbon nanotubes and few‐layered graphene. Issue 27 (22nd March 2017) - Lu, Tiemei; Ye, Huijian; Zheng, Aiai; Xu, Xilian; Xu, Chunfeng; Wang, Haiping; Sun, Li; Xu, Lixin
ABSTRACT: Herein, a facile method has been reported to efficiently prepare debundled multiwalled carbon nanotubes (MWCNT) and few‐layered graphene using a hyperbranched polyethylene (HBPE), and as hybrid fillers, their modification effects on high‐density polyethylene (HDPE) are well demonstrated. Stable dispersions of debundled MWCNT and graphene in chloroform were respectively obtained by sonication using the HBPE as stabilizer, and MWCNT/graphene/HDPE ternary nanocomposites were then fabricated by solution‐assisted premixing and subsequent melt mixing, at a fixed mass ratio of MWCNT/graphene of 3:1 and serially changed filler loadings. It is found that the MWCNT and graphene have good dispersibility in the composites, and as hybrid fillers, they can effectively form composite net‐like structure, which makes them show better modification effects on both the electrically and thermally conductive properties of HDPE, as compared to the single MWCNT. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44848. Abstract :